A Control-based Load Balancing Algorithm with Flow Control for Dynamic and Heterogeneous Servers - Siqueira, Rodolpho G. de; Figueiredo, Daniel R. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2017)
Although load balancing is a fundamental and well-studied problem in resource allocation, the ever changing scenarios and technologies in distributed systems demand new approaches and algorithms. In this context, we consider a real world scenario where servers are heterogeneous and have dynamic background loads not controlled by the load balancer. In such scenarios, classic round robin policy or novel joint the shortest queue policy are not effective. We propose a load balancing algorithm that dispatches requests to a set of heterogeneous servers according to their CPU availability using a feedback control loop to prevent overloading. We implement this policy and evaluate its performance in real and controlled scenarios. Our evaluation indicates the proposed algorithm is more effective in distributing load than other classic policies, in particular when background load is dynamic.